Role of Resilience in Cement Supply Chain Points - Uma Sankar Mishra; Subhendu Patnaik; Bibhuti Bhusan Mishra (International Journal of Supply Chain Management, 2019)
The literature on supply chain management suggests that there are many mutually dependent points in the supply chain and each supply chain points is sensitive to the performance of one another. In course of business, interrelated supply chain activities might get destabilized because of the man-made or natural factors. It is posited that human factor (resilience) may contribute to restoring the balance. The main purpose of this study is to examine the relationships of resilience with performance. This study included 258 respondents from four large private cement manufacturing firms. Correlation, regression, and structural equation modeling were used to test the hypotheses. Findings suggest that resilience is positively related to employee performance in the supply chain. Since resilience is found to be positively related with performance practitioners can use this insight and develop resilience of their employees through training interventions.Keywords: Resilience, Performance, Structural Equation Modeling, Supply Chain, Cement Industry